Carbon Cost Accounting Model for the Indonesian Cement Industry - Monika Handayani; Phaureula Artha Wulandari; Rika Novyanti (Citakonsultindo, 2025)
This study develops a carbon cost accounting model tailored to the Indonesian cement industry, a sector that represents one of the nation’s largest industrial contributors to CO₂ emissions. While Indonesia introduced a carbon tax in 2022, its effective implementation has been constrained by the lack of clear technical guidelines for integrating carbon costs into corporate accounting systems. Drawing upon environmental management accounting, legitimacy theory, stakeholder theory, and the triple bottom line framework, this research proposes a structured model to identify, measure, and allocate carbon-related costs—namely emission allowances, carbon taxes, and abatement costs—within financial reporting. Using a mixed-methods approach that combines qualitative insights from industry practitioners with quantitative analysis of economic and sustainability data, the model addresses critical gaps in current practices, enhances transparency, and supports regulatory compliance. Beyond compliance, it provides a strategic tool for improving resource efficiency, reducing emissions, and strengthening competitiveness in a carbon-constrained economy. Ultimately, the proposed framework seeks to empower Indonesian cement companies to better manage their environmental impact, align with global sustainability targets, and enhance long-term economic resilience.